Additive and nonadditive genetic components in passion fruit - dos Santos, Carlos Eduardo Magalhães; Bruckner, Claudio Horst; Cruz, Cosme Damião; de Siqueira, Dalmo Lopes; Rosado, Luciana Domiciano Silva (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to assess the additive and nonadditive genetic components in passion fruit productive and qualitative traits, in order to determine the occurrence of dominant genetic effects. Twelve F1 hybrids, obtained from two different populations using design II of Comstock and Robinson, were studied. During the first and second years (off-season and first crop, respectively), the following traits were evaluated: number of fruits per plant, estimated yield, fruit mass, skin mass, pulp mass, longitudinal length, equatorial diameter, skin thickness, content of total soluble solids, total titratable acidity, and pulp color. The yield for the 2004/2005 biennium was estimated from the total number of fruit multiplied by the average fruit mass. Dominant effects and, therefore, heterosis were observed in the first year for fresh matter mass, pulp mass, skin mass, and fruit equatorial diameter, and, in the second year, for fruit equatorial diameter and pulp color. There was predominance of addictive effects for number of fruits and fruit mass. Heritability values are indicative that the evaluated population can be used to form a base population to promote recurrent selection.